The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/wnn.0b013e318192ccc8
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Information Processing in Coma

Abstract: Results suggest a wide range of cortical information processing in coma, including semantic processing. The question is discussed of whether, and to what extent, these processing operations are related to conscious awareness of stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Despite this analysis providing non-significant results, we will nevertheless discuss them for two reasons. First, the percentage of patients exhibiting significant results at the single-patient level is similar to what has been reported in the literature on semantic categorization in comatose patients (Fischer et al, 2008; Daltrozzo et al, 2009). Second, the analysis relies on assuming that the AUC values follow a binomial distribution, which remains an untested hypothesis.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Despite this analysis providing non-significant results, we will nevertheless discuss them for two reasons. First, the percentage of patients exhibiting significant results at the single-patient level is similar to what has been reported in the literature on semantic categorization in comatose patients (Fischer et al, 2008; Daltrozzo et al, 2009). Second, the analysis relies on assuming that the AUC values follow a binomial distribution, which remains an untested hypothesis.…”
Section: Resultssupporting
confidence: 84%
“…Most previous studies included patients in later stages of coma (>4 days after coma onset in Daltrozzo et al, 2009) and used linguistic material (Fischer et al, 2008; Qin et al, 2008; Rama et al, 2010). Moreover, no study had been performed on patients treated with TH and while patients were under sedation; conditions which allow us to conclude that all these patients were, at least in the first recording, totally unconscious.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, false negatives in active paradigms have also been reported by others, (c.f. Daltrozzo et al, 2009;Harrison and Connolly, 2013;Kotchoubey, 2005;Lulé et al, 2013). Thus, it appears that the paradigm itself is not sufficiently sensitive to discriminate between different DOCs and cannot be recommended for routine clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Event-related potentials (ERPs), derivatives of the EEG obtained by signal averaging, can even be used to obtain indices of specific stages of sensory and cognitive information processing. Indeed, more than a decade of comprehensive research in this [8]- [11] and other labs [12]- [16] has demonstrated the diagnostic power of several ERPs in assessing cognitive function in behaviorally unresponsive patients. The current letter presents a novel brain wave technology that executes this kind of ERP-based test rapidly and provides a diagnostic measure that blends the clinical features of the GCS with the physiological measurement of conscious awareness.…”
Section: Introductionmentioning
confidence: 99%